Approximated Solutions to Operator Equations based on the Frame Bounds - Jamali, H.; Hemmat, A. Askari (Communications in Mathematics and Applications, 2012)
We want to find the solution of the problem ${Ł} u = f$, based on knowledge of frames. Where ${Ł} : H → H$ is a boundedly invertible and symmetric operator on a separable Hilbert space $H$. Inverting the operator can be complicated if the dimension of $H$ is large. Another option is to use an algorithm to obtain approximations of the solution. We will organize an algorithm in order to find approximated solution of the problem depends on the knowledge of some frame bounds and the guaranteed speed of convergence also depends on them.